Improving productivity of maize (Zea mays)-wheat (Triticum aestivum) cropping sequence in Mollisols using target yield approach of nutrient management - VARSHA PANDEY; AJAYA SRIVASTAVA; DEEPAK KUMAR (The Indian Journal of Agricultural Sciences, 2025)
Maize (Zea mays L.)-wheat (Triticum aestivum L.) cropping sequence holds immense significance in Mollisols, serving as a vital source of nutrition and income for millions and playing a pivotal role in global food security. The study was carried out during 2019–20 and 2020–21 at Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Uttarakhand to increase the productivity of the maize-wheat rotation in Mollisols using the Soil Test Crop Response (STCR) target yield approach. The experiment was conducetd in a randomized block design (RBD) comprised of 9 treatments, viz. T1 (Control); T2 (Recommended dose of fertilizers - RDF); T3 (STCR - Inorganic mode); T4 (STCR INM mode); T5 (75% STCR dose of nitrogen + full P and K + Green manuring with Sesbania); T6 (50% STCR dose of N + full P and K + Green manuring with Sesbania); T7 (75% Recommended dose of nitrogen + full P and K + Green manuring with Sesbania); T8 (50% RDN + full P and K + Green manuring with Sesbania); and T9 (Farmyard manure - FYM + Green manuring with Sesbania + Urd intercropping), replicated thrice. The results showed the significant improvement in maize and wheat yields in Mollisols with the STCR target yield approach, showcasing enhanced nutrient utilization. The adoption of target yield approach stands as a promising solution to enhance maize-wheat cropping sequence productivity, addressing food security challenges and promoting sustainable agriculture in Mollisols.